2015
DOI: 10.1186/s12917-015-0377-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of immune response and cytokine profiles in the bursae and spleen of chickens infected with very virulent infectious bursal disease virus

Abstract: BackgroundVery virulent infectious bursal disease virus (vvIBDV) induces immunosuppression and inflammation in young birds, which subsequently leads to high mortality. In addition, infectious bursal disease (IBD) is one of the leading causes of vaccine failure on farms. Therefore, understanding the immunopathogenesis of IBDV in both the spleen and the bursae could help effective vaccine development. However, previous studies only profiled the differential expression of a limited number of cytokines, in either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 36 publications
(57 reference statements)
2
23
1
Order By: Relevance
“…Moreover, both classical and vvIBDV were shown to induce apoptosis in an avian macrophage cell line, NCSU, at 72 hpi (Khatri & Sharma, 2007), and we have also recently shown that HD11 cells infected with vvIBDV strain UPM0081 undergo apoptosis after 24 hpi (Rasoli et al, 2015). In this study, we detected higher numbers of apoptotic cells in vvIBDV-infected BM-DCs compared to LPS-treated BM-DC at 12 and 24 hpi.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, both classical and vvIBDV were shown to induce apoptosis in an avian macrophage cell line, NCSU, at 72 hpi (Khatri & Sharma, 2007), and we have also recently shown that HD11 cells infected with vvIBDV strain UPM0081 undergo apoptosis after 24 hpi (Rasoli et al, 2015). In this study, we detected higher numbers of apoptotic cells in vvIBDV-infected BM-DCs compared to LPS-treated BM-DC at 12 and 24 hpi.…”
Section: Discussionsupporting
confidence: 70%
“…Earlier expression of proinflammatory cytokines (IL-1β, IL-6, CCL4, CXCLi1) were detected in chicken spleen compared to bursa specimens [14] may also attributed to the trigger of apoptotic event in spleen isolated IgM+ cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 and CD8 cells populations appeared to increase in the BF, decrease in the thymus (particularly in the cortex), and show an increasing trend for CD4 and decreasing CD8, which was observed in the spleen in vvIBDV infected chickens (Carballeda et al, 2014), although results from work by Rodenberg et al (1994) were contradictory. It is not clear whether these higher populations are due to cell migration from the tissues to the periphery or contractions of the resident cells (Rasoli et al, 2015). Bird age and genetic background differentially modulate the activity of T cell in IBDV infections Haase, 2005, Tippenhauer et al, 2013).…”
Section: Cd4 and Cd8 Cellsmentioning
confidence: 99%
“…IBDV increase the expression of proinflammatory cytokines IL-1, IL-6, IL-18 and inducible nitric oxide synthase iNOS in the BF (Khatri et al, 2005;Liu et al, 2010) and spleen (Palmquist et al, 2006), and significantly higher levels of nitric oxide in the splenocytes (Kim et al, 1998) and DH11 cells (Rasoli et al, 2015). Moreover, IBDV upregulate IFN-β stimulated genes, including those encoding oligoadenylate synthetase (OAS), dsRNA-dependent protein kinase (PKR), myxovirus resistance (Wong et al, 2007;Lee et al, 2015b) cyclooxygenase-2 (COX-2), chemokine (IL-8) and antigen-presenting molecules (Li et al, 2007;Lee et al, 2015b).…”
Section: Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation